2019
DOI: 10.12968/bjon.2019.28.9.s29
|View full text |Cite
|
Sign up to set email alerts
|

Living with ureteric stents: a phenomenological study

Abstract: Background: patients with ureteric stents (JJ stents) have reported symptoms such as voiding dysfunction, incontinence, depression and sexual dysfunction, which have impacted on their quality of life, since the procedure was first described by Zimskind in 1967. Aim: the aim of this study was to enhance understanding of the lived experience of having a ureteric stent. Method: the research design used was hermeneutic interpretive phenomenology, underpinned by Heidegger's interpretive phenomenology. Findings: thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Indeed, it has been demonstrated that stents provoke irritating voiding symptoms, hematuria, stent incrustation and fragmentation, back pain, stent migration, infection, pyelonephritis, and ureteral trauma (12,13). These complications may significantly affect patients QoL and could explain the data in favor of mPCNL regarding psychological outcomes (14). Even though several studies demonstrated a significant difference in terms of discomfort and distress of stented and not stented patients, deeper insights are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been demonstrated that stents provoke irritating voiding symptoms, hematuria, stent incrustation and fragmentation, back pain, stent migration, infection, pyelonephritis, and ureteral trauma (12,13). These complications may significantly affect patients QoL and could explain the data in favor of mPCNL regarding psychological outcomes (14). Even though several studies demonstrated a significant difference in terms of discomfort and distress of stented and not stented patients, deeper insights are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have begun to examine the physical and psychosocial challenges of KSD from a qualitative perspective (Raja et al, 2020). These impacts tend to be characterized by frequent and painful urinary symptoms, gastrointestinal symptoms, sleep disturbances, work impacts (Ragab et al, 2020; Tran et al, 2018), impact on relationships (Raja et al, 2020) and treatment‐related anxiety (Kelly & Kelly, 2019; Ragab et al, 2020). Whilst psychological distress experienced by patients may be explained in part by the multi‐dimensional consequences of KSD, patients also report a fear of recurrence of KS (Nouri et al, 2021), anxiety about the future (Raja et al, 2020) and uncertainty of the condition (Ragab et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…This paper also explores the role ANPs can have in becoming AAA champions. [29] in an Irish study undertaken by ANPs, explored the lived experience of patients with ureteric stents. They recommend that urological nurses can enhance the patient's experience of living with a ureteric stent by providing psychological support, including pain relief and education.…”
Section: Theme 2 Emergency Advanced Nurse Practice -Emergency Care Pe...mentioning
confidence: 99%